DESCRIPTION OF HEMOGLOBIN LEVELS OF STUDENTS OF THE FACULTY OF HEALTH JENDERAL ACHMAD YANI YOGYAKARTA UNIVERSITY 2023: GAMBARAN KADAR HEMOGLOBIN MAHASISWA ASRAMA FAKULTAS KESEHATAN UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA 2023 - Ilma Sahida (Akper Kesdam I/Bukit Barisan Padang, 2023)
Background: Hemoglobin level is one of the important tests to determine whether a person passes or not to donate blood. Hemoglobin levels are influenced by several factors including nutrition, iron, physical activity, gender and age. Female studentsare a group that is prone to anemia. This is because, experiencing menstruation every month. The impact of low hemoglobin levels can cause adolescents to experience decreased concentration in learning, decreased physical fitness, and impaired growth so that their height and weight do not reach normal. Objectives: This study aims to determine the hemoglobin level of students in the dormitory of the Faculty of Health, Jenderal Achmad Yani University, Yogyakarta. Methodes: This type of research uses quantitative descriptive. The sampel in this study were residents of the Unjaya student dormitory as many as 66 students using purposive sampling technique. Data analysis using univariate analysis. Results: Based on the results of research conducted from 66 respondents, respondents with normal hemoglobin levels were 26 (39,39%). Respondents with low hemoglobin levels were 40 (60,61%). Respondents with high hemoglobin levels 0 (0%). Conclusion: The results of this study showed that the most hemoglobin levels with low hemoglobin levels or anemia were 40 (60,61%) respondents. Keywords: Hemoglobin, Students, Girls Dormitory